The psychological impact of diabetes: A practical guide for the nurse practitioner. Issue 11 (17th June 2013) - Pearce, Michelle J.; Pereira, Katherine; Davis, Ellen
Abstract Purpose To describe the psychological impact of diabetes and to present a number of practical ways that nurse practitioners (NPs) can assess and address these concerns in the context of primary care. Data sources Theory and research articles are reviewed from the fields of nursing and psychology describing the psychological problems unique to those with diabetes. A case study is provided for practical application of the clinical tools presented. Conclusions The psychological consequences of diabetes can be significant, including feelings of loss, anger, depression, anxiety, and disordered eating. There are a number of useful tools and resources for NPs to use in the primary care setting to effectively manage the multifaceted impact of diabetes on patients' lives. These tools include listening, showing empathy, comprehensive assessment of psychosocial issues, equipping patients for self‐management, encouraging self‐care, teaching stress management skills, and offering additional mental health support. Psychotherapy can help patients to address emotional and behavioral aspects of diabetes. Implications for practice Assessing and addressing the psychological aspects of illness is an important part of caring for people with diabetes. There are many tools and resources available to NPs that can be implemented with minimal training.